Early mobilization as a new pathway to improve functional mobility of cardiac patients in High dependency Unit. (29th July 2021) - Thakur, RS; Selvamani, D; Matharsa, S; Chacko, G; Francis, P; Papasavvas, T
Abstract: Funding Acknowledgements: Non funded project Background Early mobilization as a multidisciplinary team approach in cardiac High Dependency Unit-B (HDU B) helps to reduce loss of muscle strength, decrease hospital length of stay, improve functional capacity, cognitive levels, enhances the quality of care, and helps to decrease the hospitals costs. Purpose: Early mobilization means reducing the time of bed rest from admission to first activity. Based on this definition the project aimed to mobilize more than 95% of cardiac patients within 24 hours of admission by September 2019 in HDU B unit. Methods: HDU B Initiated Early mobilization program as a part of Value improvement project (VIP). Experts from multidisciplinary team (MDT) worked together to improve the functional mobility of patients. A cross section survey was conducted to identify barriers for early mobility in the unit followed by analyzing barriers through Pareto chart.  An early mobility flow chart (Level1-Passive, Level 2-Active assisted, Level 3-Active) framed in order to standardize the practice of mobilizing patients in HDU B. New changes were tested by using methodology of Plan Do Study Act. Staff education, training given regarding the implementation of early mobility protocol. Patients with mobility level 1 and 2 were identified by nurses, requested for Physiotherapy referral by Physicians. Nursing staff education on mobility assessment given an easy access of data about mobility level of patients in handoff communication, which guided the staff to decide on the need of PT consultation for each patient. In coordination with MDT team referral were also given even during weekend for the patients with mobility level 2. To engage patient and family in the early mobility program a new concept of END PYJAMA PARALYSIS was introduced. Patients with mobility level 3 were identified and encouraged to wear their own dress and move outside their room under supervision.This concept aims to build confidence in patients making them feel that they are ready to go home. Results: With support and co-operation of the MDT, this project became a highly successful project in VIP. Initially 50% of the patients has been mobilized when the program was introduced in the ward during March 2019 which increased gradually to 90% at the end of the month. After introducing the flow chart, there was increase in 93.3% by April 2019. In addition to Physio referral it went to 100% at the end April 2019. End pyjama paralysis and weekend physio referral sustained the 100% compliance to Early mobility till the end of July 2019. Active interventions of the team helped to early mobilize by 100% till the end of September 2019 and currently it is in sustainable phase. Conclusion: Early mobilization in HDU-B brought significant change in the culture of mobilization. Commitment, cooperation of MDT, a structural system and End pyjamas paralysis program are key factors of the success for the program that promoted patient safety and prevented adverse events.